The Role of Tourism in Development: A Dilemma Between Economic Growth and Mangrove Forest Degradation (A Case Study of Regencies/Cities in North Maluku Province) - Elia Radianto; Titi Susilowati Prabawa; Wilson M. A. Therik; Gatot Sasongko; Marthen Luther Ndoen (Jurnal Manajemen Hutan Tropika, 2019)
The establishment of the Morotai Island Regency as one of the 10 National Tourism Strategic Areas and Special Economic Zones is a central government strategy to accelerate the development of regencies/cities in North Maluku Province, which are still classified as underdeveloped regions in Eastern Indonesia. This study aims to analyze the influence of tourist arrival rate, price, human development index, and tourism promotion policy on economic growth by using regression of panel data of fixed-effect model (FEM) based on the feasible generalized least square (FGLS) VI method in eight regencies/cities in North Maluku Province during the period of 2012–2017. This finding shows that tourism development was closely related to economic growth, both in the short and long term. However, the development of tourism facilities and other supporting tourism facilities on the coast by coastal landfill had sacrificed the growth of coastal mangrove forests. Therefore, the local government is encouraged to issue regional regulations on the implementation of sustainable tourism businesses and educate the local community and visitors to play a role in protecting the environment of tourist destinations sustainable.